London Building Workers Lobby, 1965 (1965)
1965 1960-2000 "London Building Workers Lobby, 1965" [T0417.jpg], 1965 On 30 April, 1965, the TUC organised a conference of union executives to discuss the voluntary incomes policy proposed by George Brown, Secretary of State at the Department for Economic Affairs. The majority of the General Council supported the Labour Government and the establishment of a National Board for Prices and Incomes.